Identidad personal e identidad narrativa: La aportación de Ricœur a la cuestióm de la identidad - Villaverde, Marcelino Agís (B@belonline, 2021)
We analyze in this work the Paul Ricœur’s contribution to the question of identity, a subject treated by numerous authors from the origins of Western philosophy to the present time. The originality of Ricœurian approaches lies in presenting personal identity as the result of a narrative identity that we construct to find the sense of our life. We are, as Ricœur affirmed, a story in search of a narrator. We describe here the itinerary followed by the French philosopher in dealing with this matter in several of his works.